An Analysis of Gender Representation in Students’ Writing Recount Text - Fenyda Anggraini (UNIB Press, 2023)
The objective of this study was to determine the differences in gender representation, both male and female, in written recount texts. This study is a descriptive quantitative in which data collection techniques include giving written tests and interviews. The subjects of this study were 20 students, consisting of 10 males and 10 females, in first grade at one of the Madrasah Aliyah in the South of Bengkulu. As a result, gender representation was male in 80% and 20% of the error categories and female in 90% and 10% of the error categories. The differences between males and females were in their topics, diction, and sentence structure.